Theft and Reception of Host Cell's Sialic Acid: Dynamics of Trypanosoma Cruzi Trans-sialidases and Mucin-Like Molecules on Chagas' Disease Immunomodulation - Fonseca, Leonardo Marques da; da Costa, Kelli Monteiro; Chaves, Victoria de Sousa; Freire-de-Lima, Célio Geraldo; Morrot, Alexandre; Mendonça-Previato, Lucia; Previato, Jose Osvaldo; Freire-de-Lima, Leonardo (Frontiers in Immunology, 2019)
The last decades have produced a plethora of evidence on the role of glycans, from cell adhesion to signaling pathways. Much of that information pertains to their role on the immune system and their importance on the surface of many human pathogens. A clear example of this is the flagellated protozoan Trypanosoma cruzi, which displays on its surface a great variety of glycoconjugates, including O-glycosylated mucin-like glycoproteins, as well as multiple glycan-binding proteins belonging to the trans-sialidase (TS) family. Among the latter, different and concurrently expressed molecules may present or not TS activity, and are accordingly known as active (aTS) and inactive (iTS) members. Over the last thirty years, it has been well described that T. cruzi is unable to synthesize sialic acid (SIA) on its own, making use of aTS to steal the host's SIA. Although iTS did not show enzymatic activity, it retains a substrate specificity similar to aTS (α-2,3 SIA-containing glycotopes), displaying lectinic properties. It is accepted that aTS members act as virulence factors in mammals coursing the acute phase of the T. cruzi infection. However, recent findings have demonstrated that iTS may also play a pathogenic role during T. cruzi infection, since it modulates events related to adhesion and invasion of the parasite into the host cells. Since both aTS and iTS proteins share structural substrate specificity, it might be plausible to speculate that iTS proteins are able to assuage and/or attenuate biological phenomena depending on the catalytic activity displayed by aTS members. Since SIA-containing glycotopes modulate the host immune system, it should not come as any surprise that changes in the sialylation of parasite's mucin-like molecules, as well as host cell glycoconjugates might disrupt critical physiological events, such as the building of effective immune responses. This review aims to discuss the importance of mucin-like glycoproteins and both aTS and iTS for T. cruzi biology, as well as to present a snapshot of how disturbances in both parasite and host cell sialoglycophenotypes may facilitate the persistence of T. cruzi in the infected mammalian host.